Enhancement effect of silver nanoparticles on fermentative biohydrogen production using mixed bacteria - Zhao, Wei; Zhang, Yongfang; Du, Bin; Wei, Dong; Wei, Qin; Zhao, Yanfang (Bioresource technology, 2013)
•Appropriate concentration of silver nanoparticles favors high H2 yield.•Presence of silver nanoparticles reduces the lag phase for biogas production.•Presence of silver nanoparticles increases the H2 percentage in the biogas.•Presence of silver nanoparticles reduces alcohols yield but increase acetic yield. Silver nanoparticles were added into anaerobic batch reactors to enhance acidogenesis and fermentative hydrogen production simultaneously. The effects of silver nanoparticles concentration (0–200nmolL−1) and inorganic nitrogen concentration (0–4.125gL−1) on cell growth and hydrogen production were investigated using glucose-fed mixed bacteria dominated by Clostridium butyricum. The tests with silver nanoparticles exhibited much higher H2 yields than the blank, and the maximum hydrogen yield (2.48mol/molglucose) was obtained at the silver concentration of 20nmolL−1. Presence of silver nanoparticles reduced the yield of ethanol, but increased the yield of acetic acid. The high silver nanoparticles had higher cell biomass production rate. Further study using the alkaline pretreated culture as inoculum was carried out to verify the positive effect of silver nanoparticles on H2 production. Results demonstrated that silver nanoparticles could not only increase the hydrogen yield, but reduce the lag phase for hydrogen production simultaneously.